Control of Turbulence in a Multiple-Fan Wind Tunnel: Part 1, Control of Longitudinal Turbulence in a 2-Dimensional Wind Tunnel - WAKAFUJI, Syuji; MATSUDA, Yuji; NISHI, Akira; TSUNO, Yukihiro; OHKUR, Mitsushi (Wind Engineers, JAWE, 1994)
Many types of meteolorogical, environmental and boundary layer wind tunnels havebeen constructed to simulate atmospheric phenomena on buildings, structures andtransport of air pollutants. New types of 2-and 3-dimensional wind tunnels havebeen constructed in our laboratory, which have multiple-fans controlled by a computer. To simulate the required wind turbulence in the wind tunnel, each fan iscontrolled independently. First, the fan characteristics and its control methods toproduce the turbulence are discussed. Second, a few examples of longitudinal turbulent flow in the 2-D wind tunnel are presented.